WEB-BASED SALES DATA VISUALIZATION DASHBOARD SYSTEM FOR PARFUMKU UMKM: SISTEM DASHBOARD VISUALISASI DATA PENJUALAN BERBASIS WEB PADA UMKM PARFUMKU - Reygina Azahra; Nabila Faiza Nisa; M. Qolbin Salim; Dzikri Fathulloh; Luthfi Aditya Makarim; Dahlia Widhyaestoeti (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2026)
Although MSMEs play an important role in Indonesia's economy, they still face several challenges in entering digitalization, particularly related to the management and utilization of sales data. One of the MSME businesses, Parfumku, faces problems with inventory and sales data management that have not yet been integrated. This makes business performance monitoring and decision-making difficult. The purpose of this study is to design and develop a web-based sales data visualization system that can display information on inventory, product trends, and sales in an interactive and easily understandable manner. Requirement analysis, system design, implementation, and testing are the stages of the Rapid Application Development (RAD) method used in system development. Sales charts, trend charts, and product contribution visualizations based on sales prices are some of the data visualizations available in the developed system. User Acceptance Testing (UAT) was used to evaluate the system. The results obtained from fourteen respondents showed a percentage score of 85.71%, which falls into the very good category. The results of this study indicate that the developed visualization dashboard presents information through sales charts, while the word cloud visualization illustrates the highest revenue generated from sales. The system is easy to use and can assist Parfumku MSME in monitoring sales performance and supporting data-driven decision-making processes.